Identification and characterization of an interleukin-16-like gene from pacific white shrimp Litopenaeus vannamei. (September 2017) - Liang, Qianhui; Zheng, Jiefu; Zuo, Hongliang; Li, Chaozheng; Niu, Shengwen; Yang, Linwei; Yan, Muting; Weng, Shao-Ping; He, Jianguo; Xu, Xiaopeng
Abstract: Interleukins are a group of cytokines that play essential roles in immune regulation. Almost all interleukin genes are only found in vertebrates. In this study, an interleukin-16-like gene (LvIL-16L) was identified from Pacific white shrimp, Litopenaeus vannamei . LvIL-16L was predicted to encode a precursor (pro-LvIL-16L) with 1378 amino acids, sharing similarities with predicted pro-IL-16-like proteins from insects. The C-terminus of pro-LvIL-16L protein contained two PDZ domains homologous to the mature IL-16 cytokine of vertebrates. In tissues, LvIL-16L could be processed into a ∼36 kDa mature peptide through a caspase-3 cleavage site, which was verified by in vitro site mutation analysis and in vivo RNA interference (RNAi) experiments. The LvIL-16L mRNA could be detected in all the analyzed tissues and the expression of LvIL-16L was significantly up-regulated after immune stimulation. Using RNAi strategy, the role of LvIL-16L in immune responses was initially investigated. Interestingly, knockdown of LvIL-16L could significantly increase the mortality of the Vibro parahaemolyticus infected shrimps but reduce that of the WSSV infected shrimps, suggesting that LvIL-16L could have opposite effects on the antiviral and antibacterial immune responses in shrimp. To our knowledge, this is the first study of an IL-16-like gene in invertebrates, which could help to elucidate interleukin evolution and regulatory mechanisms of shrimp immune responses. Highlights: Study of the first invertebrate IL-16 like gene (LvIL-16L) from Litopenaeus vannamei. Identification of the mature LvIL-16L peptide. LvIL-16L plays different roles in antiviral and antibacterial immune responses.